Nutritional management and sexual condition in cattle determine differentiation in the fatty acid profile of meat - Cattelam, Jonatas; Argenta, Flânia Mônego; Alves Filho, Dari Celestino; Brondani, Ivan Luiz; Nörnberg, José Laerte; Pacheco, Rangel Fernandes; Mayer, Andrei Retamoso; Machado, Diego Soares; Teixeira, Odilene de Souza; Borchate, Daniele (Semina: Ciências Agrárias, 2021)
This study aimed at evaluating the fatty acid profile of meat from feedlot finished heifers and steers fed with high-grain diets. It was used 45 Charolais and Nellore crossbred cattle, 21 of them were heifers with an initial age of 32 ± 2 months and 359.9 ± 6.7 kg of body weight, and 24 were steers with an initial age of 20 ± 2 months and 337.6 ± 6.2 kg of body weight. The animals were distributed in the treatments according to the energy source used in the diet, being them: rice, white oats or corn, using seven heifers and eight steers for each diet. The experimental design was completely randomized, with factorial arrangement 3 x 2 (three treatments and two sexual conditions). The diet based on corn provided higher levels of pentadecylic and margaric fatty acids. Excepting elaidic fatty acid, beef from steers and heifers was similar for the different saturated and monounsaturated fatty acids evaluated. A rice-based diet is advantageous when meat production is recommended with greater participation of fatty acids from the omega-3 group. When finished in feedlot with high-grain diets, the heifers produce meat with higher conjugated linoleic acid (CLA) content and a better ratio between omega-6/omega-3 fatty acids compared to steers. These findings indicate that it is possible to modify undesirable characteristics in meat through the nutritional management of animals, searching for a product that meets the requirements of a modern population, which is redefining its principles regarding food.